Management of Adverse Events in Cancer Patients Treated With PD-1/PD-L1 Blockade: Focus on Asian Populations - Yang, Jiqiao; He, Xiujing; Lv, Qing; Jing, Jing; Shi, Hubing (Frontiers in Pharmacology, 2019)
The interaction between programmed cell death protein 1 (PD-1) receptor and their ligands programmed death-ligand 1 (PD-L1) induced exhaustions of cytotoxic lymphocytes in the tumor microenvironment, which facilitates tumor immune evasion. PD-1/PD-L1 blockade therapy, which prevents the receptors and ligands from binding to each other, disrupts the T-cell exhaustion signaling, thereby increases antitumor immunity. Inspiringly, it has revolutionized the treatment of many different types of cancers including non-small-cell lung carcinoma, melanoma, lymphoma, etc. However, with the intention of generating an anti-tumor immune response, PD-1/PD-L1 blockade may also lead to a spectrum of side effects. The profile of adverse effects of PD-1/PD-L1 blockade is not exactly the same with other immune checkpoint blockades such as blockade of cytotoxic T-lymphocyte-associated protein 4 (CTLA-4). While cutaneous, gastrointestinal and pulmonary systems are common victims, adverse events of PD-1/PD-L1 blockade might occur in any other organ systems of human body. These toxicities can be life-threatening if not managed promptly, and proper treatment intervention is imperative for optimal control and prevention of severe damage. Currently, clinical practice for the management of adverse events in PD-1/PD-L1 blockade remains sporadic and variable. Besides, the majority of initial clinical trials were carried out in Caucasian. The trials of multiple races usually included a small portion of Asian participant, and results were calculated and interpreted for the entire included subjects without any race specific conclusions. Therefore, the information of PD-1/PD-L1 blockade in Asian is far from systematic or comprehensive. Recently, as the results of clinical trials of anti-PD-1/PD-L1 agents in Asian population have been gradually released, we summarized the current evidence with a specific focus on the Asian population, hoping to outline strategies and offer guidance on the management of adverse events in cancer patients treated with PD-1/PD-L1 blockade in the Asian world.